2000
DOI: 10.1590/s0100-84042000000400007
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of xyloglucan containing protuberances in the storage cell walls of cotyledons of Hymenaea courbaril L.

Abstract: -(Occurrence of xyloglucan containing protuberances in the storage cell walls of cotyledons of Hymenaea courbaril L.). Despite the suggestions of its pectic composition, no clear evidence for this has been presented. Here we show the occurrence of such a structure in walls of cells from cotyledons of Hymenaea courbariI L. These cells are known to accumulate large amounts of storage xyloglucan in the wall and, in this case, the protuberances seem to contain this storage polysaccharide rather than pectin. A hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Pectin polymers are also found as CWSPs, notably arabinogalactan (Crawshaw and Reid, 1984;Parker, 1984;Buckeridge et al, 2000b). In cotyledons of lupin (Lupinus angustifolius), the chemical structure is a b-(1,4)-linked D-galactan with branches of a-(1,5)-Ara (Hirst et al, 1947).…”
Section: Arabinogalactanmentioning
confidence: 99%
See 3 more Smart Citations
“…Pectin polymers are also found as CWSPs, notably arabinogalactan (Crawshaw and Reid, 1984;Parker, 1984;Buckeridge et al, 2000b). In cotyledons of lupin (Lupinus angustifolius), the chemical structure is a b-(1,4)-linked D-galactan with branches of a-(1,5)-Ara (Hirst et al, 1947).…”
Section: Arabinogalactanmentioning
confidence: 99%
“…The location of storage xyloglucans may possibly explain the lack of action of the exohydrolases on the polymers but only on oligosaccharides (see below). Tiné et al (2000b) found that the storage cell walls of H. courbaril forms protuberances that make bridges between cotyledon cells that store xyloglucan. These bridges seem to hold cells together along with a middle lamella, but at the same time with intercellular spaces that are thought to be filled with water during imbibition.…”
Section: Xyloglucanmentioning
confidence: 99%
See 2 more Smart Citations
“…RGII has a backbone of HG rather than RG, with complex side chains attached to the GalA residues (Willats et al, 2006). Using chemical stains, other constituents of the primary cell wall were also detected in IPPs: cellulose in Picea (Miller and Barnett, 1993), xyloglucan in Hymenaea (Tiné et al, 2000), proteins and callose in Azolla (Veys et al, 1999).…”
Section: Introductionmentioning
confidence: 99%